Linguistic criticism - Fowler, Roger (Oxford University Press, 1996)
A particularly fruitful development in literary studies has been the application of ideas drawn from linguistics. Precise analytical methods help the practical criticism of texts, while at the same time the theory of language has illuminated literary theory. Linguistic Criticism is an accessible introduction to this often confusing subject. Fowler sets out clearly and simply a variety of analytical techniques whose application he demonstrates in discussions of a wide range of texts drawn from fiction, poetry, and drama. He concentrates on structures that relate literature to ordinary language, stressing the importance of the reader's everyday language skills. This second edition has clarified and expanded sections on the role of the reader in literary criticism and includes more twentieth-century texts and examples